A Safety Awareness Program for Women With Diverse Disabilities: A Randomized Controlled Trial. (July 2014) - Robinson-Whelen, Susan; Hughes, Rosemary B.; Gabrielli, Joy; Lund, Emily M.; Abramson, Wendie; Swank, Paul R.
Women with diverse disabilities ( N = 213), recruited through 10 centers for independent living (CILs), were randomly assigned to either a personal safety awareness program or usual care. The 8-week program, led by CIL staff, was designed to increase safety awareness, abuse and safety knowledge, safety skills, safety self-efficacy, social support, and safety promoting behaviors. All participants completed pre-, post-, and 6-month follow-up questionnaires. Results revealed that participation in a brief safety awareness program may improve safety protective factors among women with disabilities who vary widely in their experience with abuse. The program holds promise for enhancing safety among women with disabilities.